2012
DOI: 10.1517/14728214.2012.713345
|View full text |Cite
|
Sign up to set email alerts
|

Emerging biological insights and novel treatment strategies in multiple myeloma

Abstract: MM patient outcome has remarkably improved due to the use of three to four drug combination therapies including PIs and IMiDs, which target the tumor in its bone marrow microenvironment, however MM treatment remains challenging. The use of high-throughput techniques has allowed to discover new insights into MM biology. The identification of candidate therapeutic targets and availability of respective investigative agents will allow for a substantial progress in the development and implementation of personalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 215 publications
0
9
0
1
Order By: Relevance
“…Therefore, there may have been an over‐representation of ‘healthier’ patients in this analysis. Secondly, over the past decade, advances in therapies for MM, such as ASCT and the novel agents, bortezomib, lenalidomide and thalidomide, have improved patient survival (Gentile et al , ; Ludwig et al , ). Consequently, our results may be confounded by a ‘history effect’ whereby patient HR‐QoL data collected from clinical trials conducted over the course of more than 12 years may be influenced by the changing availability of certain treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may have been an over‐representation of ‘healthier’ patients in this analysis. Secondly, over the past decade, advances in therapies for MM, such as ASCT and the novel agents, bortezomib, lenalidomide and thalidomide, have improved patient survival (Gentile et al , ; Ludwig et al , ). Consequently, our results may be confounded by a ‘history effect’ whereby patient HR‐QoL data collected from clinical trials conducted over the course of more than 12 years may be influenced by the changing availability of certain treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A treatment strategy of using these drugs alone and in combinations has led to deeper responses and more durable disease control, 6,7 resulting in significantly improved survival. [6][7][8][9] Bortezomib was the first PI to be tested in the clinic; clinical trials have demonstrated its effectiveness in treating both newly diagnosed [10][11][12][13][14][15] and relapsed and/or refractory MM.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a plasma cell malignancy characterized by the presence of monoclonal protein in the blood or urine and clonal plasma cells in the bone marrow (Qiang et al , ,b; Gentile et al , ). Symptoms include hypercalcaemia, renal insufficiency, anaemia and lytic bone lesions (Rajkumar, ).…”
mentioning
confidence: 99%